Sweetness Ratings of U.S. Infant Formulas - Olson, Chelsea; Kumar, Rajesh; Talavera, Martin J.; Anderson, Christopher E.; Hanson, Jennifer A. (MDPI, 2025)
Background/Objectives: The U.S. Food and Drug Administration sets nutritional standards for infant formulas. Yet, the carbohydrate components of these formulas can vary markedly in type as well as sweetness intensity. Despite evidence suggesting sweetness can influence intake, limited research exists on the sweetness properties of infant formulas. This study evaluated the sweetness of six commonly used infant formulas in the United States. Methods: A sensory panel (n = 15) was formed by selecting individuals who achieved a 100% accuracy on three distinct sensory acuity screening tests to assess their ability to detect, differentiate, and quantify various sucrose concentrations. Following training, the panel evaluated each formula during three separate sessions using a sweetness scale from zero to fifteen, where zero represented no sweetness (distilled water) and fifteen represented extreme sweetness (16 g sucrose/100 mL of water). Differences in sweetness were determined using 3-way ANOVA (infant formula, repetition, and panelists) followed by post hoc pairwise comparisons. Results: Individual sample sweetness ratings ranged from 0 to 4.5 with a mean rating for all samples of 1.9 (±1.3). Significant differences were detected among the formulas F(5, 264) = 96.1, p < 0.0001. One formula, a standard milk-based formula, which contains no added non-lactose sugars, was rated significantly sweeter than any of the other formulas while the sweetness ratings for three formulas which all include non-lactose added sugars were significantly lower than that of the other formulas. Conclusions: The potential implications of these noted sweetness differences make this an important topic for future sensory, behavior, and health research.
Keywords: infant formula; dietary sugars; taste perception; sensory panel; sweetness